2009
DOI: 10.4197/mar.20-1.1
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Densities of Contracaecum sp. Larvae in Liza abu (Heckel, 1843) from Different Iraqi Water Bodies

Abstract: In monthly samples of Liza abu collected, June 2001-May 2002 from three localities (Hilla river, Al-Furat fish farm and Al-Mahaweel drain), Babylon province in the middle of Iraq. Fishes were infected with the third larval stage of the nematode Contracaecum sp. The infection of Contracaecum sp. larvae were analyzed according to the season, sex, host length, and sampling localities. Its prevalence and intensity was 11.9% and 1.1 larvae per fish respectively for the Winter, and the Summer had 47.6% and 3.5 larva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 19 publications
1
13
0
1
Order By: Relevance
“…Boomker (1994a) and Bergmann and Motta (2004) reported that nematode burden increases via ontogenic changes with infection being absent in juveniles but present in adults. Reasons for a greater presence of worms in larger individuals are attributed to a larger body cavity and/or the feeding preference of the second intermediate host (Aloo 1999;Al-Zubaidy 2009). These assumptions are supported by previous studies done on Barbus spp.…”
Section: Discussionmentioning
confidence: 53%
“…Boomker (1994a) and Bergmann and Motta (2004) reported that nematode burden increases via ontogenic changes with infection being absent in juveniles but present in adults. Reasons for a greater presence of worms in larger individuals are attributed to a larger body cavity and/or the feeding preference of the second intermediate host (Aloo 1999;Al-Zubaidy 2009). These assumptions are supported by previous studies done on Barbus spp.…”
Section: Discussionmentioning
confidence: 53%
“…The fact that both values of prevalence and mean intensity in nematode infections increase with the body length of the host has been noticed before by various authors who suggested that as fish growth, chances of infection are higher either due to the exposure time or the increase of the internal organs of the fish that a parasite can use to attach itself (Moravec and Scholz, 1995;Al-Zubaidy, 2009;Ahmad et al, 2018). Our data are also consistent with some studies that revealed the relation between the sexually mature fish and occurrence of nematodes, younger fish being less infected or even not infected at all than older fish (Bergmann and Motta, 2004;Szostakowska et al, 2005;Perez et al, 2009).…”
Section: Discussionmentioning
confidence: 77%
“…Contracaecum sp. is not host-specific in the larval stage (Al-Zubaidy 2009) and the larvae usually occur in the body cavity of the fish (Whitfield & Heeg 1977). They showed a variation in prevalence and reached a peak in winter, but this was not statistically significant.…”
Section: Discussionmentioning
confidence: 99%